Contemporary Advances in Sports Science - Taiar, Redha (IntechOpen, 2021)
Sports are very important and help people increase mobility, optimize performance, and reduce their risk of disease. Sporting activities can have beneficial social, cultural, economic, and psychological effects on health, wellbeing, and the environment. As such, this book discusses a range of principles, methods, techniques, and tools to provide the reader with a clear knowledge of variables improving sports' performance processes. Over three sections, chapters consider physical, mechanical, physiological, psychological, and biomechanical aspects of sports performance, sports science, human posture, and musculoskeletal disorders.